Evaluation of Budget Expenditure (Mandatory) of Education Sector in Mahakam Ulu Regency - Gregorius Lasah Higang; Fibria Indriati Dwi Liestiawati (Dinasti International Journal of Education Management And Social Science, 2025)
The limited budget of the education sector sourced from the regional budget, because only around 15% of the Mandatory Spending in the education sector is given by the Mahakam Ulu Regency government from the regional budget. Therefore, an evaluation analysis of the mandatory budget expenditure (mandatory) of the education sector in Mahakam Ulu Regency was carried out using the Joyce and Pattison Model. The post-positivism was used by collecting qualitative data through interviews and literature studies. The results of the study indicate that the mandatory output of the education sector in Mahakam Ulu Regency reflects the results of local government policies and programs, especially in remote areas. With optimal budget allocation, the main programs include the management of preschool, elementary school, junior high school, and the distribution of educators. Performance targets include the construction of four teacher/principal rooms each year with a budget of IDR 1.2 billion, as well as the development of infrastructure to create a modern learning environment; Mandatory education outcomes in Mahakam Ulu Regency show significant progress. There is an increase in access and quality of education with 38 elementary schools, 17 junior high schools, and 71 early childhood education centers in 50 villages. The school participation rate for ages 5-6 years reached 80.47% and for ages 7-15 years 99.35%, with a target of 100% in 2024. Net participation rate also increased in early childhood education, elementary schools, and junior high schools, while students' literacy and numeracy skills continued to improve. Expected length of schooling is stable at 12.5-12.6 years, and average length of schooling increased to 7.89 years in 2022, reflecting progress in access to education up to junior high school; The education budget performance indicators in Mahakam Ulu Regency show good achievements, especially in gross participation rate and net participation rate for early childhood education, elementary schools/Islamic elementary schools, and junior high schools/Islamic junior high schools. However, school participation rate-18 years and Equivalency are still constrained by data collection. The absorption of the Education Office budget is more than 70%, but administrative services, such as basic education data and salary disbursement, are less effective, reducing public satisfaction. Improvements in the administrative system are needed to improve services and public trust.